Evaluación de rendimiento de 6 líneas experimentales de Soya (Glycine max (L.) Merril), de maduración precoz en la provincia de Picota-San Martín - Saavedra Grandez, Orlando (2009)
The present investigation work had the following objectives: To evaluate and to know the productive behavior of 6 experimental lines of soya (Glycine max (L.) Merril), classified in group of Precocious maturation, to select the line or more productive lines for the ecological conditions of the Huallaga Central, for their liberation like commercial variety and to make the economic analysis of the new variety. This investigation was carried out in the I am founded of the Private Company San Fernando CORP., located in the Sector Huinge that is located to 1 km to the south, left margin of the highway Fernando Belaúnde Terry. One worked with 6 lines of precocious maturation (denominated 643; 651; 706; 798; 799; and 803), to which was applied the design of blocks totally at random, having 7 treatments with three repetitions including the witness: V - 16. The lines are coming from the Brazil and the witness is a commercial variety coming from the Agronomic Institute of Countryside. The results of the experiment were that of the experimental Lines in study the line 798 (T4), he/she obtained a yield of 2792,6 Kg/Ha, statistically similar to the V-16 (T7), considering her like a new soya variety to liberate. Among the experimental lines the one that more highlighted for their yield to part of the line 798 (T4), it was the line 651 (T2), with average of 2479,0 Kg / there is. Parameters like the number of sheaths for plant, number of grains for sheath and weight of seeds, they have influenced in the yield of the soya lines like those denominated 16 (T7), 798 (T4) and 651(T2), being characteristic of genetic origin characteristic of each one of them. The V-16 (T7) and 798 (T4), to other of having bigger yield, they have the biggest relationships benefit / cost, that is to say that when investing a sun for the production of this cultivation, a gain is obtained of being of s / .0,89 n/s for the variety 16 and s /. 0, 85 n/s for the line 798. Finally you concludes that the line to be liberated as new variety by their adaptability to the conditions of the Huallaga Central, their high yield and benefit / cost is the line 798 (T4).